Seamless handover for multicast mobile IPv6 traffic. (1st January 2014) - Abou-Khalil, Georges; Krishnan, Suresh; Pierre, Samuel
MIPv6 is an IETF protocol that manages mobility, allowing a MN to continue to be reachable after an IP address change, result of a handover. However, when multicast applications are used, this address change results in a disruption of the service, because of the packet loss that occurs while the MN is rejoining the multicast group. Hence, we propose a new multicast scheme that provides a seamless multicast service during a handover in a MIPv6 network. The proposed scheme achieves its goal by adding a new node, denoted the MBA, whose role is to buffer the packets when the MN is performing the handover. These packets would otherwise be lost. We present an analysis of the buffer sizes to find the optimal sizes. Simulation results, obtained with OPNET, show that by properly sizing the buffers, seamless multicast handover can be achieved with the proposed scheme.